THE INFLUENCE OF DEMOCRATIC LEADERSHIP STYLE AND MOTIVATION ON THE PERFORMANCE OF SABHARA MEMBERS AT TOMOHON RESORT POLICE - Vanya Monica Debora Frans; Paulus Kindangen; Shinta J. C. Wangke (Universitas Sam Ratulangi, 2023)
This study aims to figure out the influence of democratic leadership style and motivation on performance partially and simultaneously. The population in this research is 42. The sampling technique used is saturated sampling, where all members of the population are used as samples. The analytical method used is multiple linear analysis with the help of SPSS 29.0 program. The results show that partially democratic leadership style does not have a positive and significant influence on the performance of Sabhara Members at Tomohon Police. However, there is a positive and significant influence of motivation on the performance of Sabhara Members at Tomohon Police. Whereas simultaneously democratic leadership style and motivation have a positive and significant influence on the performance of SABHARA members at Tomohon resort police. Keywords: democratic leadership style, motivation, employee performance